Keselamatan Kini dan Nanti dalam Konsep Ayii dan Mobu serta Korelasinya dengan Konsep Keselamatan Paulus - Keiya, Benyamin (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2017)
Salvation is hoped by all people. Salvation is the purpose of human being to have a good life not only in the world but also in the afterlife. The question of whether it is historical or eschatological salvation as the most important in life comes up among the different religions and cultures. Culturally, people seek to find  salvation inn the world and hopefully in the hereafter. Ayii and mobu are concepts of salvation of the Ekagii tribe in Papua, Indonesia. These concepts want to give answers to the Ekagii people needing salvation in this world and in the afterlife as well. Mobu is an understanding of how a person survives in this world, but especially with regards of the material as well as the spiritual needs. Ayii is an understanding of how salvation could be experienced after death. The Ekagii people are trying to find the eternal life, ayii, in their life. This article correlates these concepts of salvation with that of Saint Paul especially in his escathology. Paul’s tension between the terms ‘already’ and ‘not yet’ is different, but in some sense similar to the cultural concepts of the Ekagii people. Paul is also providing some answers to the Christians concerning their need of salvation in the world and in the world to come. The author underlines the focus of both concepts on the process of salvation that is experienced historically and dinamically in the world.